Development of chicken manure pelleting machine for organic fertilizer production - Dichoso, Jeffrey G; Villota, Elmar M; Fabulac, Jonathan V; Malamug, Vitaliana U (Asian Journal of Agriculture and Rural Development, 2025)
This research aimed to solve the chicken manure disposal problem in the Philippines' poultry industry by developing and evaluating a pelleting machine made from local materials. The machine utilized a flat die and roller system to pelletize dried chicken manure with molasses. Following PAES guidelines and PNS-BAFPS specifications, the study assessed pellet physical properties and processing costs, considering belt speeds (650, 950, 1250 rpm) and molasses-to-chicken ratios (2:100, 3:100, 4:100) in a completely randomized two-factorial experiment. Results showed that higher belt speeds (950 and 1250 rpm) significantly increased pelleting capacity, reaching a maximum capacity of 160.09 kg/hr and 165.12 kg/hr, respectively. An optimal 3:100 molasses ratio yielded 98.02% pelleting efficiency and 98.29% recovery, exceeding PAES minimum standards. Additionally, the produced pellets met PNS-BAFPS physical characteristics, and the pellet durability is comparable to that of the highest pellet durability index of 80%. However, moisture content exceeded recommended levels (47.07-48.63%), indicating the need for drying. At a processing cost of ₱4.26/kg, the machine provides an economical solution, with future development focused on incorporating drying technologies and conducting nutrient analyses.